2017
DOI: 10.1186/s40066-017-0100-1
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder farmers’ adaptation to climate change and determinants of their adaptation decisions in the Central Rift Valley of Ethiopia

Abstract: Background:The agricultural sector remains the main source of livelihoods for rural communities in Ethiopia, but faces the challenge of changing climate. This study investigated how smallholder farmers perceive climate change, what adaptation strategies they practice, and factors that influence their adaptation decisions. Both primary and secondary data were used for the study, and a multinomial logit model was employed to identify the factors that shape smallholder farmers' adaptation strategies. Results:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
246
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(358 citation statements)
references
References 20 publications
64
246
4
1
Order By: Relevance
“…Maize. Although maize is the major crop and the mainstay of farmers in the villages, its production is highly constrained by soil moisture stress, intra-and inter-seasonal rainfall variability and dry spells [42], and poor soil nutrients [23]. In response to the unfavorable climatic conditions, the use of early-maturing maize is an interesting option for farmers.…”
Section: Improved Crop Varietiesmentioning
confidence: 99%
“…Maize. Although maize is the major crop and the mainstay of farmers in the villages, its production is highly constrained by soil moisture stress, intra-and inter-seasonal rainfall variability and dry spells [42], and poor soil nutrients [23]. In response to the unfavorable climatic conditions, the use of early-maturing maize is an interesting option for farmers.…”
Section: Improved Crop Varietiesmentioning
confidence: 99%
“…Nearly 90% of farmers can perceive climate change, and approximately 85% try to manage this by adjusting cropping patterns and planting dates, by irrigation management, and by increasing the agricultural inputs (Belay, Recha, Woldeamanuel, & Morton, ). Belay et al () indicated that the most important practice farmers used to reduce the impacts of climate change especially in the lowland was to adjust crop planting dates and crop varieties. The cropping pattern in the HID has also changed during the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been done on factors affecting farmers' adaptations to climate change in the various areas of Ethiopia (BERHANU & BEYENE, 2015;DERESSA ET AL., 2010;TESFAY, 2014;ERENA & GEMECHU, 2016;BELAY ET AL., 2017;AMARE & SIMANE, 2018;TESSEMA ET AL., 2013;TAZEZE ET AL., 2012). Although various climate change response strategies are rigorously researched, the extent of the practice of each adaptation and mitigation strategy adapted from the CRGE initiatives in rural areas and farmers' perception towards these strategies are not well addressed.…”
Section: Background Of the Studymentioning
confidence: 99%